The systemic crisis of climate change: clinical and political reflections (2013) and The EcoSystemic Return: clinical and political implications (2021) - Kearney, Philip (Murmurations: Journal of Transformative Systemic Practice, 2021)
In this special issue on the EcoSystemic Return, we have the honour of our Revival Paper being the 2013 paper by esteemed systemic ecology activist from Ireland, Philip Kearney. This paper is a reminder that the systemic community did not heed warnings about ecology issued by Gregory Bateson in the 1960s and 70s. In 2013, Phil Kearney reminded us again. The original paper is followed by a fresh piece of writing for this special issue. Philip Kearney reignites his passion and anger, his critical analysis and call to action for this protracted phase of climate change complacency. Sincere thanks and appreciation to Jim Sheehan and colleagues of Feedback: Journal of the Family Therapy Association of Ireland for permission to re-print the 2103 article which had the vision to provide a platform for this important work.